ChemInform Abstract: Extending the Family of Oxygen Ion Conductors Isostructural with La2Mo3O9. Issue 4 (31st January 2013) - Voronkova, V. I.; Kharitonova, E. P.; Orlova, E. I.; Belov, D. A.
Abstract X‐ray diffraction shows that compounds isostructural with the oxygen ion conductor La2Mo2O9 exist in the ternary systems La2Mo2O9—Nd2W2 O9—Nd2Mo2O9 and La2Mo2O9—Pr2W2 O9—Pr2Mo2O9 over wide single‐phase regions.